PENGARUH THREAT EMOTIONS, KEPERCAYAAN MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU ANLENE ACTIFIT - Dhio Panji Pratama; Hari Susanta Nugraha; Sri Suryoko (Universitas Diponegoro, 2014)
In process of consumer buying decision, the process begin with consumer’s cognitive judgement as the positive or negative pressure. There are many factors that affect consumer’s buying decision of Anlene Activit product, such as threat emotions, brand trust, and price. The problem of this research is the competitive rate of Anlene Activit product that become more tight. Meanwhile, Anlene Activit is the market leader and it has to face the competitiveness among many others brand, such as Hi Lo, Calcimex, Produgen and other brand. So this become a problem that threathened the position of Anlene Activit. This research is quantitative research, with questionnaire technique. Sampling texhnique used is judgement sampling, that are 100 rspondents that consumed AnleneActivit at Semarang. Analysis method used arevalidity and reliability testing,simple regression, multiple regression, t test and F test. Based on the result, the conclusion are: Threat emotionAnleneActivit included high enough category. The effect is 49,9% toward buying decision.Brand trustAnlene included high category. The effect is 78,3% toward buying decision. Price Anlene Activit included competitive category, The effect is 30,2% toward buying decision. Buying decision AnleneActivit included high category. Threat emotion,Brand trust, price have significant effect toward buying decision partially and simultaneously.